(untitled) (Journal of Philosophy Culture and Political Science, 2020)
Recent events in the world and radical changes in the development of human civilization have once again proved the importance of the concept as “science”. The article examines how the People’s Republic of China develops science and innovation to realize the concept of the “Chinese Dream”. Until now, on the world market, China’s industrial export policy has been carried out through the expansion of its cheap goods. This strategy is no longer effective in the competition. This is due to the need for hightech production: the creation and development of high-quality products. The current economic growth and the current foreign economic situation, the accelerated modernization of the Chinese economy are favorable on a modern technological basis. The introduction of a complex of high technologies in organizations and mechanisms representing the national innovation system and industry is reflected in the search and updating of new products and technologies in the form of scientific knowledge. The article is based on the principle of the scientific and technological development of China in the political, economic, trade, humanitarian spheres, taking place in the modern world. In addition, some issues of Kazakh-Chinese bilateral cooperation in the field of science were analyzed. The paper were used the theory of “soft power” in international relations and the Chinese concept of “harmonious world”. Key words: People’s Republic of China, theoretical foundations of China’s foreign policy, “Chinese dream”, soft power.